(untitled) (The International Journal for Scientific Research, 2025)
The study aimed to identify the role of high-performance human resource management practices in achieving organizational leadership, applying them to telecommunications sector companies in the Kingdom of Saudi Arabia. The study relied on a descriptive-analytical approach and used a simple random sampling method to collect data. The study sample consisted of 377 individuals. The study found a high level of high-performance human resource management practices, as well as a high level of organizational leadership in telecommunications sector companies. It also demonstrated a statistically significant positive impact of high-performance human resource management practices on achieving organizational leadership in telecommunications sector companies in the Kingdom of Saudi Arabia. The study recommended that telecommunications sector companies work to increase levels of job security for employees, provide a high degree of independence and flexibility in work performance, provide good opportunities for promotion, and provide opportunities for employees to develop their personal and professional skills. It also recommended evaluating the impact of the decisions they make.